Nanocomposite Zinc Oxide-Chitosan Coatings on Polyethylene Films for Extending Storage Life of Okra (Abelmoschus esculentus) - Laila Al-Naamani; Joydeep Dutta; Sergey Dobretsov (Nanomaterials, 2018)
Efficiency of nanocomposite zinc oxide-chitosan antimicrobial polyethylene packaging films for the preservation of quality of vegetables was studied using okra Abelmoschus esculentus. Low density polyethylene films (LDPE) coated with chitosan-ZnO nanocomposites were used for packaging of okra samples stored at room temperature (25 °C). Compared to the control sample (no coating), the total bacterial concentrations in the case of chitosan and nanocomposite coatings were reduced by 53% and 63%, respectively. The nanocomposite coating showed a 2-fold reduction in total fungal concentrations in comparison to the chitosan treated samples. Results demonstrate the effectiveness of the nanocomposite coatings for the reduction of fungal and bacterial growth in the okra samples after 12 storage days. The nanocomposite coatings did not affect the quality attributes of the okra, such as pH, total soluble solids, moisture content, and weight loss. This work demonstrates that the chitosan-ZnO nanocomposite coatings not only maintains the quality of the packed okra but also retards microbial and fungal growth. Thus, chitosan-ZnO nanocomposite coating can be used as a potential coating material for active food packaging applications.